2015
DOI: 10.1016/j.radonc.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA repair pathway choice in cancer cells after proton- and photon-irradiation

Abstract: A differential DNA damage response with enhanced susceptibility of HR-deficient tumor cells to proton-irradiation and increased sensitivity of photon-irradiated tumor cells to NHEJ inhibitors were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 18 publications
7
105
2
Order By: Relevance
“…For example, homologous recombination is required for the repair of DSBs in late S- and G2-phases of the cell cycle. It has been shown that defective homologous recombination increases the RBE for cell survival [44, 68, 7072]. There are research efforts toward identifying biomarkers to identify patients with RBE values either low or high compared with the overall patient population [44, 68, 70].…”
Section: Rbe Variations In Patientsmentioning
confidence: 99%
“…For example, homologous recombination is required for the repair of DSBs in late S- and G2-phases of the cell cycle. It has been shown that defective homologous recombination increases the RBE for cell survival [44, 68, 7072]. There are research efforts toward identifying biomarkers to identify patients with RBE values either low or high compared with the overall patient population [44, 68, 70].…”
Section: Rbe Variations In Patientsmentioning
confidence: 99%
“…However, the increased resistance to protons is less pronounced than the increased resistance to x-rays. The results indicate that DNA damage induced by protons is less amenable to DNA-PKcs–dependent repair than damage induced by x-rays, a result that is not inconsistent with studies showing that homologous recombination-defective cells (NHEJ competent) exhibited an increased proton RBE [24, 25]. …”
Section: Discussionmentioning
confidence: 68%
“…A review of the literature suggests a trend for a higher proton RBE in x-ray–resistant versus x-ray–sensitive cells [2023]. However, in studies using wild-type and DNA-PKcs–deficient or DNA-PKcs–inhibited cells (or other key constituents of NHEJ), a significant proton RBE difference between sensitive and resistant cells has generally not been observed [15, 16, 24, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…This difference is due to a difference in the complexity of DNA damage induced by these two radiation types. A higher level of clustered DNA damage lesions and locally multiply damaged sites (LMDS) has been previously reported after proton irradiation [15]. Observed differences might also be due a difference in cell death pathways [16].…”
Section: Resultsmentioning
confidence: 75%